2018
DOI: 10.1080/10652469.2018.1464567
|View full text |Cite
|
Sign up to set email alerts
|

Newton diagram of positivity for 1F2 generalized hypergeometric functions

Abstract: As for the positivity of 1 F 2 generalized hypergeometric functions, we present a list of necessary and sufficient conditions in terms of parameters and determine the region of positivity by certain Newton diagram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…To investigate the sign of 1 F 2 generalized hypergeometric function Φ, we shall make use of the following general criterion recently established by the authors [5], which will be applied subsequently in other occasions as well.…”
Section: Positivity In the Unrestricted Casementioning
confidence: 99%
“…To investigate the sign of 1 F 2 generalized hypergeometric function Φ, we shall make use of the following general criterion recently established by the authors [5], which will be applied subsequently in other occasions as well.…”
Section: Positivity In the Unrestricted Casementioning
confidence: 99%
“…In this section we aim to extend the aforementioned positivity criterion of [8] for the generalized hypergeometric functions of type (1.8).…”
Section: Rational Extension Of Newton Diagrammentioning
confidence: 99%
“…with parameters a > 0, b > 0, c > 0. In the recent work [8], to be explained in detail, a positivity criterion for the functions of type (1.8) is established in terms of the Newton diagram associated to {(a + 1/2, 2a), (2a, a + 1/2)}. Due to certain region of parameters left undetermined, however, it turns out that an application of the criterion to (1.7) yields Theorem A immediately but does not cover the missing region T either.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonnegativity of the G function in the integrand combined with γ − 1 ≥ 0 completes the proof. In a nice recent paper [5] the authors found the exact range of positive parameters α, β 1 , β 2 that ensure the inequality 1 F 2 (α; β 1 , β 2 ; x) ≥ 0 for all real x. This range can be described as follows: for α > 0 let P α denote the convex hull of the points (α m , ∞), (α m , α M ), (α M , α m ), (∞, α m ) in the plane (β 1 , β 2 ), where α m = min(2α, α + 1/2), α M = max(2α, α + 1/2).…”
Section: (319)mentioning
confidence: 99%